SISTEM INFORMASI PEMETAAN OBJEK WISATA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Akbar, Muhamad Aulia; Fauziyah, Fauziyah; Zulkarnain, Iskandar (Jurnal Ilmiah Sistem Informasi, 2023)
Location Pamijahan District in Bogor Regency, West Java Province, Indonesia. Pamijahan District has many natural and artificial tourist attractions that many tourists can visit. Currently, data collection and dissemination of information regarding tourist attractions and mapping of tourist attractions is still not optimal. That means the tourists don't know about tourist attractions are in Pamijahan District, Bogor Regency. From the description of the problem, a Website-Based Tourist Object Mapping System was designed and built in Pamijahan District, Bogor Regency, which expected to be able to solve this problem. For analysis and design methods, researcher uses Unified Modeling Language (UML). The Tourist Attraction Mapping System in Pamijahan District, Bogor Regency, uses the PHP and MySQL programming languages ​​as its database. The method used in designing this information system is the System Development Life Cycle (SDLC) method. With this tourist attraction mapping system, hoped that it can help Pamijahan District, Bogor Regency in data collection and mapping, as well as assist tourists in finding tourist attractions in Pamijahan District, Bogor Regency